Probabilistic description of the dispersion of vehicular exhaust fine particles - Gili, Mon Bryan Z. (2014)
A code is developed in stimulating the dispersion of vehicular exhaust fine particles from a stationary tailpipe. A new approach in determining the gas flow, accounting for turbulence, is presented for an unbounded system. The approach is probabilistic, based on the molecular-kinetic theory of heat. It is more convenient than existing Eulerian techniques in terms of computational efficiency. A flexible approach is used in the simulation to fit the dispersion patterns of experimental exhaust emission. Simulated dispersion patterns of particles are compared to experimental dispersion of exhaust from a real vehicle tailpipe to verify the accuracy of the simulation. It is assumed that particulate matters follow the path of exhaust emission. The simulation program is used in determining the mass identity of particulates at the vicinity of the source. Results show that the stimulated pattern are narrower compared to the experimental observations. It is because of: 1) the temperature profile created by the heated tailpipe; 2) the difference in size of particles that are not accounted for in the simulation; and 3) due to the fact that the particles are the only one being simulated, ignoring the gaseous phase of emission. In general, the simulated dispersion patterns of particles are in good agreement with the experimental dispersion pattern of vehicular exhaust. he new approach is effective in investigating the transport of particulate matters.--Author's Abstract
Thesis (Bachelor of Science)--University of the Philippines Baguio, 2014.
Includes bibliographical references (leaves 72-73).
Keywords: Air -- Pollution -- Measurement; Computer simulation